Java Programming Simplified : From Novice to Professional - Start at the Beginning and Learn the World of Java - Dar, Muneer Ahmad (BPB Publications, 2020)
This book has been designed in such a manner so as to make anyone understand the Java language, with a lot of practical examples implemented on the Eclipse platform. This book comprehensively covers all the concepts of Java, starting with the installation of Java and the usage of IDE for Java development and efficiently covers all required topics of Java language with some advanced concepts like JDBC and event handling in Java